Impelemetasi Metode Montsessori dalam Menanamkan Nilai-Nilai Pendidikan Agama Islam Anak di RA Marzukiyah Praya, Lombok Tengah - Muhibbin, Muhibbin; Harjanty, Rokyal (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to prepare teachers in implementing the Montsessori method in instilling PAI values ​​in children and knowing the successes of teachers in instilling PAI values ​​in children at RA Marzukiyah. Type of qualitative research. The instruments used in this research were the researchers themselves and notebooks. Data collection techniques use observation, interviews and documentation. The results of this research show that in applying the Montsessori method in instilling the values ​​of Islamic religious education in children, there are 2 things that need to be paid attention to, namely preparation and delivery. delivery, communication skills, provoking questions and teaching aids to support the smooth learning process. and the teacher's success in instilling the values ​​of Islamic religious education in children using the Montsessori method in the form of changing attitudes and behavior for the better and children becoming independent.